(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Profitability and Value Added of Tofu-Tempe Industry (Case Study of the Main Tempe Sari Tofu Industry, Denpasar City). Indonesia is an agrarian country which means that the agricultural sector plays an important role in the overall national economy. Agriculture in a broad sense consists of five sub-sectors, namely food crops, plantations, livestock, fisheries and forestry. One of the agricultural products from the food crop sector is soybeans. Soybean is a daily consumption need of the Indonesian population and most of the population consumes soybeans so that it has become a staple food. One of the foods made from soybeans that is a typical food of Indonesia is tofu and tempeh. Tofu and tempeh are mostly produced by home industries. The purpose of this study is to analyze the structure of the cost of tofu and tempeh, analyze the added value of tofu and tempeh as well as the profitability of the tofu and tempeh business. The method used is the analysis of costs, break-even points, profitability and value added. The problem raised from this study is that researchers try to see the level of profitability of tofu and tempeh businesses and the added value generated from processing soybeans into tofu and tempeh. The results of this study indicate that each of the tofu and tempeh businesses can generate profits but greater profits are obtained from the tofu business. Soybean processing that is done provides added value to tofu and tempeh.